Refugee Articulations of Health: A Culture-Centered Exploration of Burmese Refugees' Resettlement in the United States. Issue 6 (12th May 2021) - Kumar, Rati
ABSTRACT: Grounded in the culture-centered approach that emphasizes dialogic engagement with communities at the margins to disrupt mainstream health discourses, this article explores articulations of health by the Burmese refugee community in the United States post resettlement. Due to forced migration, often fleeing violent political regimes in their home countries and surviving itinerantly in refugee camps and host countries, they face further disenfranchisement upon resettlement as a subset of immigrants who are thrust into an unfamiliar sociocultural setting with marginal federal support. Against this backdrop, the present research explores the narratives of Burmese refugees in the United States through in-depth interviews focusing on their meaning-making practices surrounding health and displays of agency in the face of structural healthcare barriers. The participants' narratives articulate health as communal and familial safety in contrast to the mainstream discourse of disease prevention and individual lifestyle choices. They describe structural barriers to healthcare access in the form of the employment-insurance nexus, and also an intricate web of lack of access to health services resulting from linguistic isolation. Within such constraints they locate agency by utilizing community networks as mediators for infrastructural and cultural access and engage in practices seeking out providers with interpreters from within the Burmese community, as well as utilizing technology such as listservs and e-mails through informal networks often ignored by mainstream healthcare providers in the community.